2021
DOI: 10.1021/acsami.1c01443
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Sub-Terahertz All-Dielectric Lens for Arbitrary Manipulation of Quasi-Nondiffractive Orbital Angular Momentum Waves

Abstract: Terahertz (THz) vortex waves carrying orbital angular momentum (OAM) hold great potential in dealing with the capacity crunch in wireless high-speed communication systems. Nevertheless, it is quite a challenge for the widespread applications of OAM in the THz regime due to the beam divergence and stringent alignment requirement. To address this issue, an all-dielectric lens (ADL) is proposed for the arbitrary manipulation of quasi-nondiffractive THz OAM waves (QTOWs). On the basis of the concept of the optical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 56 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Selected methods to meet metasurface fabrication challenges. (a) Commercial 3D printing: an example to produce orbital-angular momentum with sub-terahertz metasurface [122]. Reprinted with permission from [122].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…Selected methods to meet metasurface fabrication challenges. (a) Commercial 3D printing: an example to produce orbital-angular momentum with sub-terahertz metasurface [122]. Reprinted with permission from [122].…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…[37] All-dielectric terahertz metagratings have been used in high-efficiency manipulation of diffraction distribution. [38] The all-dielectric terahertz metalenses have been proposed for flexible manipulation of orbital angular momentum waves, [39][40][41] generation of Airy beam, [42] spinmultiplexed controls, [43,44] achromatic focusing, [45] etc. A varifocal 6G meta-device with a fully tunable range of focal spots is designed by the meta-antennas with reasonably incorporating and rotating several phase profiles.…”
Section: Introductionmentioning
confidence: 99%
“…Metasurface, a two-dimensional artificial microstructure with periodic or aperiodic arrangement, can flexibly manipulate the magnitude and phase of electromagnetic (EM) waves. The functions of beam scattering, polarization conversion, radar cross-section reduction, and asymmetric transmission are realized by arranging metasurface elements. Compared to the traditional methods, a metasurface has the advantages of low cost, low loss, easy fabrication, and multiple functions that can be applied for OAM generation. It is reported that a single metasurface can be designed for dual-mode OAM generation . This method gives a new way to generate OAM beams.…”
Section: Introductionmentioning
confidence: 99%